Gambaran Kecemasan Sosial Pada Remaja SMA Negeri Di Kecamatan Medan Kota Pada Masa Pandemi COVID-19 Tahun 2022 - Nathalyna, Hanna; Ompusunggu, Henny Erina Saurmauli; Roderthani, Ita L. (Universitas HKBP Nommensen, 2025)
Background: Anxiety disorders are a type of mental health condition that is common in society. One of the most common types of anxiety is social anxiety (SA), which is a condition in the form of a real and persistent fear of social situations. Nearly 70% of people had received the vaccine during the Covid-19 pandemic and had begun to actively conduct out their activities outside, which led to an increase in social anxiety. Objective: The purpose of this research was to characterize social anxiety in senior high school students in the Medan City District in 2022 during the Covid-19 pandemic. Methods: This study used a cross-sectional design and was descriptive in nature. There was 130 respondents in senior high school at Medan Kota District in 2022 who were chosen by the cluster selection technique. Results: In this study obtainbed 130 respondents, the level of social anxiety in senior high school adolescents at Medan City District were mild 45.4%, moderate 50,8% and severe 3.8%. Conclusion: The majority level of social anxiety in senior high school adolescents at Medan City District during the Covid-19 pandemic were mild to moderate in both male and female genders. Keywords: social anxiety, adolescent.